The Brexit and investors' fear - Shaikh, Imlak (Array, 2018)
This paper investigates most important implied volatility indices of Eurozone, Asia-Pacifi c, Africa, Canada and USA on the event of Brexit election of UK. Since the international economic events signal new information to market participants, the Brexit event has gauged in the 12 global markets’ volatility indices such as VFTSE, VIX, VDAX, VSMI, VSTOXX, VXJ, VHSI, VKOSPI, NVIX, VASX, VXIC and SAVI. A high fear of index about 20-36% has been noticed on the day of Brexit decision. Abnormal returns and cumulative abnormal returns on volatility index are found to be positive, while majority of global equity markets have reported negative stock returns on this event. To investigate the ‘fear-and-greed’ of investors on this historical event, a window of 11 -day has been considered. The findings suggest that investors’ degree of over-reaction on Brexit decision was very disappointing and fueled concerns on the future investment and portfolio choices. The key volatility indices were on the rise prior to the decision, while the market noticed astray and breached its normal range on the day of Brexit referendum. The findings suggest that market participants have diverted their funds into other safer investment outlets due to Brexit effects.